Biolubricant production from castor oil using iron oxide nanoparticles as an additive: Experimental, modelling and tribological assessment. (15th September 2022) - Ahmad, Uzair; Raza Naqvi, Salman; Ali, Imtiaz; Saleem, Faisal; Taqi Mehran, Muhammad; Sikandar, Umair; Juchelková, Dagmar
Graphical abstract: Highlights: Synthesis and evaluation of a new potential biolubricant from castor oil. Modified castor seed oil showed potential physiochemical properties using iron oxide as an additive. ANN based production and optimization was successfully achieved. Abstract: The study presents the production of biolubricant from castor oil using Fe3 O4 nanoparticles and ethylene glycol in a transesterification process, as an additive. Operational parameters such as FAME/alcohol, catalyst loading, and temperature were optimized. The reaction was complete after two hours at 160 °C, giving a yield of 94 %. To enhance the physiochemical properties of modified castor seed oil (MCSO), Fe3 O4 nanoparticles and ethylene glycol were used. The biolubricant yield was also predicted using artificial neural networks (ANN). The multilayer perceptron (MLP)-based ANN showed a linear correlation between the output and target values at different temperatures, the amount of catalyst, and the alcohol/FAME ratios during training, testing, and validation. The tribological properties of the biolubricant produced (MCSO + ethylene glycol + 0.5 % Fe3 O4 nanoparticles) showed the lowest coefficient of friction (almost 50%) and 40% decreased wear compared to raw castor seed oil and other biolubricant samples produced.